The Influence Of Inflation, And Interest Rate Levels On The Stock Price Index Of The Indonesian Stock Exchange - Grasela, Yemima; Ompusunggu, Dicky Perwira; Suherman, Suherman; Doti, Aprilya; Pasha, Audina Walia; Sedek, Melki (Jurnal Ilmiah Wahana Pendidikan, 2025)
Macroeconomic changes in Indonesia will greatly affect the Indonesian economy and all industries throughout Indonesia. The capital market is a driver of the national economy through its role as a source of corporate financing and another way for investors to invest. In the capital market, the Composite Stock Price Index (IHSG) plays a crucial role because this index can be a barometer of economic health in a country. High inflation, interest rates will lower stock prices. This study aims to see the impact of inflation and interest rates on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange (IDX). The analysis method uses an example of multiple linear analysis. The data used in this study means annual data for the period 1993-2023. The first hypothesis test was accepted and an inflation value of 0.021 was obtained. The results of the second hypothesis test were accepted and obtained from the interest rate value of 0.001. From the statistics, it was concluded that the inflation variable had a negative and significant effect on the IHSG. The interest rate variable had a negative and significant effect on the IHSG. Simultaneously, the independent variables, namely inflation, exchange rates and interest rates, had a significant effect on the IHSG. Through this study, we can conclude that macroeconomic changes, especially inflation and interest rates, have a significant impact on the IHSG convoy at the Indonesia Stock Exchange. Changes in these factors can affect investor sentiment and thus, hypnotize overall stock prices. Therefore, stakeholders in the capital market need to pay close attention to macroeconomic developments, including inflation rates and interest rates, in making investment decisions.